Регіональна специфіка релігійних інституцій українського суспільства - Яремчук, Сергій; Яремчук, Сергей; Yaremchuk, Serhii (My University, 2016)
У статті охарактеризовано регіональну специфіку релігійних інституцій українського суспільства. З’ясовано класифікацію регіональної структури України, яка використовується державою для статистики релігійних організацій. Державна статистика виділяє Західний (сім областей), Північно-Центральний (девʼять) та Південно-Східний (вісім) регіони. При цьому дані щодо анексованого Російською Федерацією Криму й м. Севастополя з 01 січня 2015 р. не подаються. Визначено кількісні параметри мережі релігійних організацій в Україні за регіонами та областями. Проаналізовано регіональну специфіку найбільших віросповідань і конфесій України. This article describes the regional specificity of religious institutions of Ukrainian society. It is shown classification of regional structure of Ukraine, which is used for state statistics of religious organizations. The quantitative parameters of the network of religious organizations in Ukraine are determined by areas and regions. Center of religious life is in the Western and North-Central regions of the country where concentrated three-quarters of all the network of religious organizations in the country. However, continuing the trend towards a more equal distribution of religious network, and the center of religious life somewhat shifted from the West to the Center. Saturation religious network in the Western region gives reason to believe that it actually created the institutional network confessional organizations, sufficient to meet the religious needs of the faithful. As a result, it reduced the growth dynamics. There are regional in nature prevalence of major faiths Ukraine, especially Catholic and Orthodox. Although quantitative indicators of institutional network, none of the existing denominations in Ukraine do not have a dominant advantage in any of its regions, there is dominance in certain areas and, therefore, the comparative advantage in some regions. In particular, there is a relative majority of Ukrainian Orthodox Church in the North Centre and the South. In the East, there are a relative majority Ukrainian Orthodox Church and Protestant organizations. In the West, there is a relative majority of organizations belonging to the Ukrainian Greek Catholic Church. According to the dynamics of the geography of religions and their construction of buildings for religious purposes the regional character of biggest Ukrainian churches will persist in the near future.
Regional Specificity of Religious Institutions of the Ukrainian Society
Keywords: регіон; область; конфесія; релігійна організація; area; region; confession; religious organization